Selaginella subchaetoloma (Sect. Heterostachys; Selaginellaceae), a new species from Southwest China - Fang, Shao-Li; Li, Yu-Xin; Zhang, Li-Bing; He, Zhao-Rong; Zhou, Xin-Mao (Phytotaxa, 2023)
A new lycophyte species, Selaginella subchaetoloma, is described. This species is relatively abundant in Southwest China. Materials of this species were previously identified as S. chaetoloma, but a detailed morphological study shows that the new species differs by plants with creeping sterile part and ascending fertile part and dorsal leaves with abruptly short-acuminate apex. Molecular phylogenetic results indicate that S. subchaetoloma and S. chaetoloma are not closely related.